Penerapan Activity Based Budgeting (ABB) Pada Anggaran Operasional Kantor Dinas Pendidikan Provinsi Sulawesi Utara - Binilang, Maydeleine; Wokas, Heince R. N.; Datu, Christian V. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
The research focuses on the implementation of Activity Based Budgeting (ABB) in the operational budget of the Education Department of North Sulawesi Province, Indonesia. It evaluates the effectiveness of ABB as a tool for enhancing financial accountability and efficiency in the public sector. The study adopts a qualitative approach, utilizing interviews, direct observations, and documentation to gain a comprehensive understanding of the budgeting process. It compares the conventional budgeting methods with ABB, examining budgetary procedures, accountability, and the alignment of financial reports with legal regulations. The analysis reveals that ABB provides a more detailed and accountable framework, addressing issues of underfinancing and overfinancing by identifying cost drivers, calculating basic units for each activity, and totaling costs for activities. This allows for a more accurate and transparent financial management, leading to significant improvements in budgetary clarity and accountability compared to previous years. The study finds that the Education Department's implementation of ABB in 2021 has not only enhanced the precision of financial reporting but also improved the strategic allocation of resources. The findings suggest that ABB can effectively address discrepancies in budget reporting and enhance the financial management of public institutions. The research concludes that the Education Department of North Sulawesi Province should continue using ABB to maintain its current high level of financial performance and responsibility, and recommends its adoption by other governmental entities seeking to improve financial management and transparency. Keywords: Operational Budget, Public Sector Management Accounting, Fund Realization Report.